La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Centre de recherche interuniversitaire sur la littérature et la culture au Québec [CRILCQ], 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Alanis Obomsawin: Lifework - Hill, Richard William; Peleg, Hila; Haus der Kulturen der Welt (Prestel Publishing, 2022)
"One of today's most important documentary filmmakers, Alanis Obomsawin has dedicated her life's work to shining a light on the injustices experienced by Canada's Indigenous people. This retrospective monograph features an extensive interview with Obomsawin and includes stills and reflections on her entire career including her most recent series devoted to the rights of Indigenous children. Never shying away from controversy, Obomsawin's films have played a critical role in exposing ongoing systemic bias towards Indigenous populations-from fishing rights and education to health care and treaty violations. Obomsawin is also a graphic artist, and she incorporates her often dream-inspired etchings and prints into many of her films. This volume includes illuminating essays exploring Obomsawin's practice and mission as well as personal commentary from collaborators, archival materials, and photographs from the filmmaker's personal life and professional exploits. As Obomsawin closes in on her ninth decade of life-and fifth decade behind the camera-this beautifully illustrated record of her astounding body of work and tireless efforts on behalf of Indigenous peoples and culture is an inspiring celebration of the power of film to dramatically change the course of history"– Provided by publisher.

“Before I made fims, I was singing” - Obomsawin, Alanis; Gagnon, Monika Kin (Alanis Obomsawin: Lifework, 2022)

Étude patrimoniale sur le katajjaniq - Gadoua, Marie-Pierre (Publications Nunavik, 2021)
Ce livre présente une résumé exhaustif de l’étude effectuée sur le katajjaniq, suite à la désignation de cette pratique à titre de premier élément du patrimoine immatériel québécois.

Dream visions: The Art of Alanis Obomsawin - Obomsawin, Alanis (Perceval Press, 2021)

L’intermédialité autochtone dans l’œuvre de Natasha Kanapé Fontaine : mémoire, oralité et territoire - Morin-Martel, Florence (Université de Montréal, 2018)
Ce mémoire explore la notion d’intermédialité autochtone au sein de l’oeuvre de Natasha Kanapé Fontaine. Les imbrications entre les médias seront notre point d’appui pour penser les questions de l’esthétique dans l’art autochtone actuel. Par le biais de la représentation d’un média dans un autre, nous aborderons ainsi la réactualisation des traditions orales telles que le conte, le mythe, le chant et le tambour au sein des productions de cette artiste. Notre parcours observera les structures intermédiales qui mettent en exergue la mémoire ainsi que les connaissances ancestrales. Les croisements entre l’identité et le territoire seront également discutés dans l’optique des représentations intermédiales. Ainsi, les phénomènes d’affirmation et de réactualisation des savoirs se déploient par l’utilisation de divers médias. De ce fait, la résistance environnementale et culturelle ainsi que la néo-oralité sous-tendent l’oeuvre de l’artiste et s’expriment à travers les territoires imaginaires et médiatiques.

Laura Niquay. Vivre et s’affirmer au féminin attikamekw - Audet, Véronique (Cahiers du CIÉRA, 2017)

L'âme en tannage de Natasha Kanapé Fontaine : Souveraineté orale, territoriale et mémorielle - Marcoux, Gabrielle (Canadian Review of Comparative Literature / Revue Canadienne de Littérature Comparée, 2017)

Paroles inuites : création et transmission dans la chanson du Nunavik - Duvicq, Nelly (Recherches amérindiennes au Québec, 2016)
Among the forms of oral history, the song, within the Inuit culture, was general practice and quite versatile. Inheriting this tradition, the contemporary Inuit song has risen in popularity starting in the 1970’s and has not diminished since. Within the literary field, the lyrics to the Inuit songs demonstrate a remarkable vitality in which the author-composers explore various aesthetics, navigate languages and transmit a part of their culture. Taking into consideration the historical context, this article aims to reflect on the formal evolution of the modern Inuit song and examine the relations that are maintained through more traditional portrayals. Finally, the ultra-contemporary body of musical works in Nunavik is notable for being particularly trilingual yet reveals an upsurge of texts in Inuktitut. What significance will this have on the overall discourse?
Publisher: Recherches amérindiennes au Québec
Keywords: Inuit literature; Inuit songs; Inuktitut; Nunavik; canción inuit; chanson inuite; inuktitut; literatura inuit; littérature inuite; oralidad; orality; oralité

Listening to "Mes lames de tannage": Notes toward a Translation - Moyes, Lianne (Canadian Literature, 2016)

Native Classical: Musical Modernities, Indigenous Research Methodologies and a Kanienkéha (Mohawk) Concept of Non:wa (Now) - Witzleben, John Lawrence (Université du Maryland, 2014)
In this dissertation I explore how Indigenous methodologies that foreground cultural advocacy, revitalization, and education can be articulated using Indigenous language and cultural metaphor in research on North American Indian composers. Toward this end, I apply the Kanienkéha (Mohawk) concept of "non:wa" or "now" that also refers to three modes of perception–the now of the past, the present, and the future–toward understanding the intersection of innovation and tradition in classical Native music. This research joins the existing discourse that critiques binary oppositions separating Indigenous tradition (as past) and innovation (as present and future). Through interviews, fieldwork, and musical analysis, I illustrate Native values of interconnectedness, relationality, continuity, politics, and soundscapes in the processes of Native composition as well as the resultant works, I explore how these, in turn, may be understood through the application of Indigenous research techniques. In collaboration with a cohort of contemporary musicians, I look primarily at two Navajo composers–Raven Chacon and Juantio Becenti–and examine my own work as a composer, performer, and ethnomusicologist of Kanienkéha descent to explore the following questions: How can the topic of classical Native music best be served by using Indigenous methodologies in fieldwork, research, and representation and What is classical Native Music and is it different from other contemporary classical music styles? Drawing on the teachings of Indigenous dotahs (elders/teachers), the scholarship of ethnomusicologists, and examining oral and written tradition while using language and cosmology as cultural metaphors, I present a variety of possibilities for looking at Indigenous music through Indigenous eyes. Rather than offering a set of conclusions, I offer a set of tools for discussion and reflection: 1) how we might understand a definition of classical Native music; 2) how we are part

Innu nikamu - L’Innu chante. Pouvoir des chants, identité et guérison chez les Innus - Audet, Véronique (Presses de l'Université Laval, 2012)
Le présent ouvrage porte sur l’expression musicale populaire contemporaine des Innus du Québec et du Labrador (Canada). Les chants et musiques innus sont abordés dans une perspective d’affirmation identitaire et de guérison sociale liées aux processus de décolonisation et de revalorisation de la culture. L’ouvrage concerne plus précisément les Innus des communautés de Uashat mak Mani-utenam et d’Ekuanitshit situées sur la côte nord du golfe du Saint-Laurent. La création et la diffusion de chansons populaires en langue innu-aimun sont devenues depuis peu un phénomène très important dans la plupart des communautés innues. Ces chansons s’inspirent à la fois des modes traditionnels de relation au son et au monde, de la tradition de chants chrétiens en langue innu-aimun ainsi que des musiques de violoneux, country, folk, rock et des divers courants actuels. Malgré ces multiples influences, elles révèlent une attitude musicale propre aux Innus, en continuité avec un mode d’être ancestral, où le chant confère du pouvoir sur soi-même et dans le monde environnant. Ancrées dans l’expérience contemporaine, ces musiques sont des agents de transformation qui prennent aussi part au processus de guérison de l’être innu.

Wendat Song and Carnival Noise in the Jesuit Relations - Bloechl, Olivia (Native Acts: Indian Performance, 1603–1832, 2011)

Jeunesse, musique et rituels chez les Atikamekw (Haute-Mauricie, Québec) : ethnographie d'un processus d'affirmations identitaire et culturelle en milieu autochtone - Jérôme, Laurent (Université Laval, 2010)

"Eskimo chicks and word warriors": the creative cultural spaces of Elisapie Isaac and Taqralik Partridge - Foot, Johanna Maria (Université Carleton, 2008)

Alanis Obomsawin: The Vision of a Native Filmmaker - Lewis, Randolph (University of Nebraska Press, 2006)
In more than twenty powerful films, Abenaki filmmaker Alanis Obomsawin has waged a brilliant battle against the ignorance and stereotypes that Native Americans have long endured in cinema and television. In this book, the first devoted to any Native filmmaker, Obomsawin receives her due as the central figure in the development of indigenous media in North America.

Oralité et culture vocale inuit - Le Goff, Philippe (Revue DEMéter, 2003)

Native American Contemporary Music: The Women - Diamond, Beverley (The World of Music, 2002)
This article explores issues raised in interviews with traditional and contemporary Native American musicians and recording artists of the 1990s. It exemplifies how they view their roles vis à vis traditional gender structures and community obligations, how they draw upon different media to communicate their messages, and how they use their work as a form of social action. Their narratives reveal a wide variety of strategies by which they negotiate the double consciousness and multiple relationships of their lives, balancing historically rooted values and traditions with modern ones. I attempt to develop a feminist interpretation that is respectful of the cultural values these women expressed in their conversations with me.
Publisher: [Florian Noetzel GmbH Verlag, VWB - Verlag für Wissenschaft und Bildung, Schott Music GmbH & Co. KG, Bärenreiter]

Inuit Throat-Games and Siberian Throat Singing: A Comparative, Historical, and Semiological Approach - Nattiez, Jean-Jacques (Ethnomusicology, 1999)
Publisher: University of Illinois Press

A Bosnian Sephardic Woman in Kahnewake, Quebec - Cohen, Judith R. (Canadian Woman Studies/Les cahiers de la femme, 1996)

Alanis Obomsawin - Kivi, K. Linda (Canadian Women Making Music, 1992)

Music and gender in the sub-arctic Algonkian area - Diamond, Beverley (Women in North American I[*****] Music: Six Essays, 1989)

The Morphology and Phonology of Katajjait (Inuit Throat Games) - Bagemihl, Bruce (Canadian Journal of Linguistics/Revue canadienne de linguistique, 1988)
A linguistic theory can be considered to have explanatory force if it may be extended to a body of facts considerably beyond the domain for which it was originally conceived. In general, the further the new domain is from the original, the greater the support that accrues to that theory. In this paper, a number of developments within current morphological and phonological theory will be utilized in the analysis of an extraordinary form of vocal behaviour, the katajjait (sg. katajjaq) or throat games of the Canadian Inuit. The result will be a revealing account of the structures of these katajjait, as well as a remarkable confirmation of principles of linguistic theory from a domain which has been hitherto unreported in the linguistic literature.

Sémiologie des jeux vocaux Inuit - Nattiez, Jean-Jacques (Semiotica, 1987)
Keywords: Pas de lien web

Musique inuit au Québec arctique : contribution à une méthode d'analyse en anthropologie de la musique - Montpetit, Carmen; Veillet, Céline (Les Cahiers de l'ARMuQ, 1984)

Some Aspects of Inuit Vocal Games - Nattiez, Jean-Jacques (Ethnomusicology, 1983)
Publisher: University of Illinois Press

The Rekkukara of the Ainu (Japan) and the Katajjaq of the Inuit (Canada): A Comparison - Nattiez, Jean-Jacques (The World of Music, 1983)

Comparisons within a Culture: The Example of the Katajjaq of the Inuit - Nattiez, Jean-Jacques (Cross-Cultural Perspectives on Music, 1982)

Pour l'adéquation de la transcription en ethnomusicologie : l'exemple du katajjaq - Berthiaume-Zavada, Claudette (Canadian University Music Review, 1980)
Keywords: Music

Le katajjaq : un jeu inuit traditionnel - Beaudry, Nicole (Études Inuit Studies, 1978)
Katajjaq, a traditional Inuit game Katajjait — the traditional Inuit throat-games — display unusual musical properties and for that reason they have been submitted to extensive musicological analysis. Furthermore, they also constitute a particularly rich example of traditional Inuit game behaviour. The present article aims at backing that statement through an analysis of Inuit games from Central Arctic, based on available written information¹.This analysis enables us to define the katajjaq not only in terms of formal properties, but also in terms of social functions. This analytical definition is achieved by comparing katajjaq with some of the Inuit game mechanisms. le katajjaq, un jeu inuit traditionnel Le katajjaq ou jeu de gorge inuit à l'origine lointaine, se caractérise par des propriétés musicales exceptionnelles. Ce jeu vocal a donc fait l'objet d'analyses musicologiques approfondies. Par ailleurs, il illustre particulièrement bien le système ludique inuit traditionnel. Nous cherchons ici à confirmer cette hypothèse, à la suite d'une étude par les textes¹ sur les jeux inuit de l'Arctique central en général. A la lumière de cette étude, nous tâchons de définir le jeu de gorge, tant par ses fonctions sociales que par son comportement formel et ce, en comparaison avec quelques mécanismes des jeux inuit traditionnels.
Publisher: Association Inuksiutiit Katimajiit Inc.

Toward Transcription and Analysis of Inuit Throat-Games: Macro-Structure - Beaudry, Nicole (Ethnomusicology, 1978)
Publisher: University of Illinois Press

Toward Transcription and Analysis of Inuit Throat-Games: Micro-Structure - Charron, Claude (Ethnomusicology, 1978)
Publisher: University of Illinois Press

Entre cri et chant. Les katajjait, un genre musical féminin - Saladin d'Anglure, Bernard (Études/Inuit/Studies, 1978)
The growing popularity in the West of various graphic or plastic expressions of contemporary (or prehistoric) Inuit art has overshadowed other aspects of Inuit art — particularly traditional music, within which throat games represent a most fascinating genre. Indeed, some of the first western travelers who attended a katajjaq performance were to pay a high price to have their curiosity satisfied — as we shall see in the following documents. The anthropologist cannot escape this fascination either, for the katajjait constitute a complex and ambiguous genre, belonging to cry and language, song and dance, game and music, ritual and performance, expressing Inuit symbolism on the relationship between man and woman, the relationship to nature and the supernatural and reflecting elements of the social structure since the performance of katajjait requires cooperation and sometimes gives rise to competition between performers. Le succès croissant en occident des différentes expressions graphiques ou plastiques de l'art inuit contemporain (ou préhistorique) a masqué d'autres aspects de l'art inuit, en particulier l'art musical traditionnel au sein duquel les jeux de gorge (notamment les katajjait) constituent un genre fascinant. Plusieurs des premiers voyageurs occidentaux qui y assistèrent en firent l'expérience à leurs dépens comme nous le verrons dans les documents qui suivent. Genre fascinant aussi pour l'anthropologue en raison de sa complexité et de son ambiguïté qui le font relever à la fois du cri et du langage, du chant et de la danse, du jeu et de la musique, du rite et de la performance; en raison également et de sa dimension symbolique lorsqu'il traite du rapport à la nature, du rapport au surnaturel et du rapport homme-femme, et de sa dimension sociologique à travers la coopération nécessitée par son exécution et la compétition parfois organisée entre les exécutants.

Recherches en ethnomusicologie: les katajjait chez les Inuit du Nouveau-Québec - Montpetit, Carmen; Veillet, Céline (Études/Inuit/Studies, 1977)